(untitled) (Bangladesh Journal of Botany, 2023)
Twenty eight pea genotypes were evaluated for their genetic variability attributes under sub-tropical conditions of Himachal Pradesh during Rabi, 2021. The estimates of phenotypic coefficient of variation (PCV) and genotypic coefficient of variation (GCV) were high for plant height and pod weight. High heritability along with high genetic advance was observed in days to first flower, node at which first flower appear, days to 50 % flowering, pod length, pod weight, number of primary branches per plant, plant height, number of pods per plant and number of seeds per pod. Pod yield was positively and significantly correlated with pod length, pod weight, pod width, pod girth, number of pods per plant, number of seeds per pod, shelling percentage and TSS. The pod length exhibited highly positive and direct effect on pod yield followed by pod weight and plant height. Therefore, selection based on these traits could be effective for higher pod yield in pea genotypes. Bangladesh J. Bot. 52(4): 907-914, 2023 (December)